Methodical approaches in experimental modelling of non-alcoholic fatty liver disease - N. V. Bivalkevich; Yu. K. Denisenko; T. P. Novgorodtseva (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To generalize literature data on ways of non-alcoholic fatty liver disease (NAFLD) modelling in experimental animals, to reveal advantages of various techniques, to present results of original studies on diet-induced NAFLD at rats.Key points. Data of the literature and author’s original data on experimental NAFLD modelling are presented. Today‘s methods of NAFLD modelling can be divided into two extensive groups: induction of liver disease by genetic mutation, and phenotypic development of NAFLD due to alimentary factor. Genetic models are subdivided into two categories. In the first the liver of laboratory animals is the main pathogenic target, metabolic disorders develop insignificantly (lines of animals with of Acetyl-CoA oxidase gene deletion, knockoutmice for methionine-adenosyl transferases-1А gene and animals with deleted specific hepatic phosphatase and tensin homologue gene). Genetic models of NAFLD developing on background of obesity and metabolicsyndrome represent the second category (animals, with leptin gene deletion – ob/ob, mice resistant to leptin action, – db/db and transgenic mice with excessive expression of styrene-regulating element of protein-1 isoform. Diet-induced models of NAFLD are engendered by modulation of various alimentary factors. They include methionine choline-deficient diet, fructoseenriched diet and various variations of high-fat diet. At diet-induced NAFLD the liver undergoes a complex of histological and metabolic disorders to the high extent close to clinical symptoms of this disease in humans.Conclusion. There is a set of various ways of NAFLD modelling in animals. Numerous methods can be used for confirmation or refutation of NAFLD pathogenesis hypotheses. It is necessary to choose the optimal way of NAFLD modelling, allowing to reveal certain part of pathologic mechanisms of disease and to determine strategy of hepatotropic treatment according to determined task.